Performance Evaluation & Economic Analysis of Mini/Micro Hydel Plants (MHPs) Installed in Gilgit-Baltistan (GB) - Muneeb Hussain(00000172243); Dr. Parvez Akhtar (USPCAS-E, NUST, Islamabad, 2019)
TH-142
Keywords: MS-ESE Thesis MS Thesis